Material properties and local stability of WAAM stainless steel equal angle sections. (15th July 2023) - Evans, Sian I.; Xu, Fangda; Wang, Jie
Highlights: Experimental tests on 3D printed 316L stainless steel stub columns and tensile coupons have been carried out. Two sets of manufacturing parameters have been used to achieve two different build thicknesses. Geometric analysis highlights the effect of the manufacturing parameters. The stabilities of 12 EAS are found and compared to results and predictions from literature, EC3 and the CSM. A new characteristic geometric dimension has been defined for predicting the buckling behaviour of slender WAAM sections. Abstract: An experimental study has been carried out to investigate the material properties and local stabilities of outstand WAAM 316L stainless steel plates. A series of equal angle section (EAS) stub columns and corresponding sample plates for tensile coupon extraction were fabricated employing two sets of manufacturing parameters in order to achieve two print thicknesses. The tensile coupons were extracted from the sample plates along different printing directions, and the tensile test results indicated a high degree of anisotropy while displaying satisfactory material ductility according to the Eurocode 3 requirements. The EAS stub columns covered a wide range of plate slendernesses and their geometric profiles were 3D laser scanned and analysed prior to the compression tests. The failure modes and load carrying capacities of the WAAM EAS stub columns were analysed, showing generally lower resistances compared to conventional rolled counterparts in the high slenderness range. Assessed against the test data, the Continuous Strength Method is shown to be suitable for designing stocky WAAM stainless steel plates. For the design of slender WAAM stainless steel plates, the effective width equation in Eurocode 3 is shown to be applicable, however, the calculation should be based on the new characteristic geometric dimension proposed. Based on this, it is further demonstrated that the thicker printing strategy adopted in the current study would have a higher effective thickness to overall thickness ratio, hence more efficient builds than the thinner printing strategy.